"They steals". (1st December 2020) - McDonough, Tom
BAND (2009), Adam Pendleton's first foray into filmmaking, was an ambitious collage of voices from the late 1960s and music by the contemporary indie band Deerhoof. Its sources are here unpacked in order to parse the complicated dialogue Pendleton establishes with the radical past and its ambivalent echoes in the present. The film is understood as an early exemplar of the artist's concept of "Black Dada" ‐ his attempt to link historical and current struggles for equality through evocations and echoes of experimental practices across America's racial divide.